Identificación y abundancia de seis virus y un espiroplasma en infecciones simples y mixtas en campos de maíz en Veracruz, México. - Aguilera Aguirre, S.; Rodriguez-Escobar, G.; Romero-González, V. N.; Osorio-Acosta, F.; López-Romero, G.; Silva-Rosales, L. (Revista Bio Ciencias, 2019)
Plant viruses are important agricultural pathogens because they cause significant losses in economic crop yield and quality. They can occur in single or mixed infections interfering with plant development. Diseases caused by these viruses are found throughout the maize-growing regions of the world and can cause significant losses for producers. Additionally, the Corn stunt spiroplasma (CSS) is able to co-infect maize plants together with phytopathogen viruses, increasing losses in this crop. In this study, using DAS-ELISA tests, we detected Maize dwarf mosaic virus (MDMV), Sugarcane mosaic virus (SCMV), Maize chlorotic mottle virus (MCMV), Maize stripe virus (MSpV), Brome mosaic virus (BMV), Maize white line mosaic virus (MWLMV), and CSS in single and mixed infections in a survey made in the State of Veracruz. Up to four different viruses were identified in mixed infections with SCMV, the most prevalent virus; followed by MDMV and CSS. This is the first report of simultaneous infections with more than two viruses in maize plants in Mexico.